Auditoría de gestión a la industria láctea pasteurizadora Tanilact, ubicada en la parroquia Tanicuchí, perteneciente al cantón Latacunga, provincia de Cotopaxi, en el período comprendido del 1 de enero al 31 de diciembre del 2014 - Toaquiza Carrera, Pamela Elizabeth (2016)
The current thesis was developed at "TANILACT" Pasteurizing with the objective; to Apply a Management Audit, by using management indicators that allow determine the level of accomplishment with each objectives and the level of efficiency, efficacy and effectiveness of the industry. The company is considered medium turn production because of daily production, look for through continuous improvement to achieve comply with its objectives and goals planned in its strategic plan, primary tool to study administrative growth. Regarding methodology, research is a descriptive nature that allowed us to evaluate the management of the company, the research design is framed in a field, considering that the data was collected directly from reality. For data collection stage techniques such as interviews and surveys were used….